Optimization of parametric balanced modulator based on frequency symbolic method - Shapovalov, Yuriy; Mandziy, Bohdan; Bachyk, Dariya (Publishing House of Lviv Polytechnic National University, 2012)
Application of the frequency symbolic method for analysis of established modes of linear periodically time-variable (LPTV) circuits to solving an optimization task conditioned by the control of their asymptotic stability is considered. The results of optimization of a parametric balanced modulator with respect to the criterion which is based on calculation of the parametric transfer functions approximated by Fourier trigonometric polynomials are presented. Розглянуто застосування частотного символьного методу аналізу усталених режимів лінійних параметричних кіл до розв’язування оптимізаційної задачі за умови контролю їх асимптотичної стійкості. Наведено результати оптимізації параметричного балансного модулятора.
Оптимізація параметричного балансного модулятора на основі частотного символьного методу
Keywords: linear periodically time-variable (LPTV) circuits; frequency symbolic method; asymptotic stability; optimization; objective function; function-characteristic